Season to season - Ganeri, Anita, 1961- (Oxford : Heinemann Library, 2006)
Explains why seasons occur, and looks at some of the patterns in nature that are repeated every year with the changing of the seasons.
Nature's patterns -- Four seasons -- Why are there seasons? -- Seasons around the world -- Spring -- Nature in spring -- Summer -- Nature in summer -- Fall -- Nature in fall -- Winter -- Nature in winter -- Two seasons -- World seasons map.
Includes index.
3.2
K-3.
K-3
Keywords: Seasons -- Juvenile literature; Seasons; Seasons